Overview of the Judge's Forgiveness Concept Its Relation to The Legal Interests of Criminal Victims (RKUHP Concept Study) - Yusuf, Muhammad Rifai; Wati, Briliyan Erna; Harun, Muhammad; Nurhayati, Tri (Walisongo Law Review (Walrev), 2021)
Judge forgiveness (rechterlijk pardon) is a new concept in the Draft Criminal Code (RKUHP) which authorizes judges not to impose a crime even though the defendant is proven guilty with several provisions as a condition of forgiveness. The position of the victim becomes important to discuss regarding the existence of this concept because the defendant who should be responsible for his actions can be released from the charge, on the other hand, the victim as the object of the crime, in general, is the party who has suffered losses for his legal interests. So, this concept ideally accommodates the interests of the victim adequately as a condition for forgiveness. The urgency of the victim's position in the concept was rechterlijk pardon further elaborated through a study entitled "An Overview of the Concept of Judge (Forgiveness Rechterlijk Pardon) concerning the Legal Interests of Criminal Victims (Concept Study of the 2019 RKUHP)". The focus of this research problem is to find out the history and concept of judge forgiveness in the RKUHP and to further review the concept of judge forgiveness about the legal interests of victims of criminal acts. This research is juridical-normative research using a historical approach, a comparative approach, and a conceptual approach. Sources of data used are data secondary consisting of legal materials (primary, secondary, tertiary). The method of collecting data is through literature or document studies and presented in a descriptive-analytical manner. The results showed that the formulation of rechterlijk pardon since the first RKUHP (1993) was motivated by the desire to include the goals and guidelines of punishment as a general principle of the Indonesian criminal system. While the concept is based on the "idea of balance" from the main elements of public interest and individual interests (actor-victim), actions and inner attitudes, certainty, flexibility, and justice. The current formulation does not represent this idea because the formulation is incomplete and clear regarding the terms of forgiveness so that from the victim's side there is uncertainty about the protection of his legal interests.Pemaafan hakim (rechterlijk pardon) merupakan konsep baru dalam Rancangan Kitab Undang-Undang Hukum Pidana (RKUHP) yang memberi kewenangan kepada hakim untuk tidak mengenakan pidana meskipun terdakwa terbukti bersalah dengan beberapa ketentuan sebagai syarat pemaafan. Posisi korban menjadi penting didiskusikan terkait keberadaan konsepsi, sebab terdakwa yang seharusnya mempertanggungjawabkan perbuatannya dapat dibebaskan dari tuntutan itu, di sisi lain korban sebagai objek kejahatan secara umum adalah pihak yang mengalami kerugian atas kepentingan hukumnya. Maka konsep ini idealnya mengakomodir kepentingan korban secara memadai sebagai syarat adanya pemaafan. Urgensitas kedudukan korban tersebut dalam konsep rechterlijk pardon dielaborasi lebih lanjut melalui penelitian dengan judul “Tinjauan Terhadap Konsep Pemaafan Hakim (Rechterlijk Pardon) Kaitannya dengan Kepentingan Hukum Korban Tindak Pidana (Studi Konsep RKUHP 2019)”. Fokus permasalahan penelitian ini adalah untuk mengetahui sejarah dan konsep pemaafan hakim dalam RKUHP serta meninjau lebih jauh konsep pemaafan hakim kaitannya dengan kepentingan hukum korban tindak pidana. Penelitian ini merupakan penelitian yuridis-normatif dengan menggunakan pendekatan historis, pendekatan perbandingan, serta pendekatan konseptual. Sumber data yang digunakan adalah data sekunder yang terdiri dari bahan-bahan hukum (primer, sekunder, tersier). Metode pengumpulan data dilakukan melalui studi kepustakaan atau dokumen dan disajikan secara deskriptif-analitis. Hasil penelitian menunjukkan bahwa perumusan rechterlijk pardon sejak RKUHP pertama (1993) dilatarbelakangi oleh kehendak memasukkan tujuan dan pedoman pemidanaan sebagai prinsip umum sistem pemidanaan Indonesia. Sedangkan konsepsinya didasarkan pada“ ide keseimbangan” dari unsur pokok kepentingan umum dan kepentingan perorangan (pelaku-korban), perbuatan dan sikap batin, kepastian, fleksibilitas dan keadilan. Rumusan saat ini belum merepresentasikan ide tersebut disebabkan formulasi yang tidak lengkap dan jelas perihal syarat-syarat pemberian maaf sehingga dari sisi korban terdapat ketidakpastian perlindungan atas kepentingan hukumnya.